(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Henry's short story "The Last Leaf," first published in 1907 in his collection "The Four Million", is a deeply moving narrative stories that learns topics of hope, sacrifice, and the human spirit. Set in Greenwich Village, the story goes around two young artists, Johnsy and Sue, and their elderly neighbor, Mr. Behrman. O. Henry presents an inspiring and heartbreaking story that is brilliantly told via the perspectives of these characters. In this essay, I will share my personal thoughts and analysis of "The Last Leaf," highlighting its emotional side and the long-lasting effect it has had on my reading.